THE COMPENSATION OF ELECTRIC RUBBED WITH THE MUTUAL LOAD OF THE TRACTION ELECTRIC MACHINES ACCORDING TO THE HOPKINSON’’S SCHEME - Afanasov, A. M. (Science and Transport Progress, 2009)
The conditions of compensation of electric losses at the test of hauling electric engines by the Hopkinson’s scheme are considered.